Effects of Family Doctor Contract Services on the Health-Related Quality of Life Among Individuals With Diabetes in China: Evidence From the CHARLS - Wang, Lingjie; Liu, Wenbin (Frontiers in Public Health, 2022)
Abstract Background: Family doctor contract service (FDCS) has played a key role in diabetes management in China since 2016. The influence of FDCS on the physiological indexes of individuals with diabetes has been examined, however, little attention has been paid to its effect on the Health-Related Quality of Life (HRQoL). This study aims to fill this knowledge gap by evaluating the effect of FDCS on the HRQoL of individuals with diabetes. Methods: We have identified 382 individuals with diabetes receiving all follow-up surveys in 2013, 2015 and 2018 from the China Health and Retirement Longitudinal Study (CHARLS). The HRQoL of the included individuals were estimated using results from the SF-36 questionnaire. The Propensity Score Matching with Difference-in-Differences (PSM-DID) approach was applied to quantify the effect of FDCS on the HRQoL among individuals with diabetes. A robust test was performed by setting the 2015 data as the treatment group for the placebo test. Results: The mean score of role-emotional (RE) increased from 54.25 to 61.63 among those who signed up to receive FDCS, while the corresponding score decreased from 57.77 to 51.04 among those who did not receive FDCS. Results from the regression analysis indicated that the use of FDCS was associated with significant improvement in RE (+14.10, p=0.04) among individuals with diabetes. We did not find a statistically meaningful association between the FDCS and any of the other HRQoL domains: physical functioning, role-physical, bodily pain, general health, vitality, social functioning, and mental health, respectively. The robustness analysis of the model indicated that the results were robust. Conclusion: The FDCS for diabetes in China was associated with a significant improvement in RE. Due to a limited time since the launch of FDCS (i.e., 2016), the recipient's physical health was not found to be markedly improved. In future, more attention of FDCS could be paid to the physiological health of individuals with diabetes. And psychological services also need to be maintained and not slackened. At the same time, it is strongly recommended to pay more attention to HRQoL of individuals with diabetes and more comprehensive health.